ZO-2 favors Hippo signaling, and its re-expression in the steatotic liver by AMPK restores junctional sealing. Issue 2 (3rd April 2022) - González-González, Laura; Gallego-Gutiérrez, Helios; Martin-Tapia, Dolores; Avelino-Cruz, José Everardo; Hernández-Guzmán, Christian; Rangel-Guerrero, Sergio Israel; Alvarez-Salas, Luis Marat; Garay, Erika; Chávez-Munguía, Bibiana; Gutiérrez-Ruiz, María Concepción; Hernández-Melchor, Dinorah; López-Bayghen, Esther; et al.
ABSTRACT: ZO-2 is a peripheral t ight j unction (TJ) protein whose silencing in renal epithelia induces cell hypertrophy. Here, we found that in ZO-2 KD MDCK cells, in compensatory renal hypertrophy triggered in rats by a unilateral nephrectomy and in liver steatosis of o bese Z ucker (OZ) rats, ZO-2 silencing is accompanied by the diminished activity of LATS, a kinase of the Hippo pathway, and the nuclear concentration of YAP, the final effector of this signaling route. ZO-2 appears to function as a scaffold for the Hippo pathway as it associates to LATS1. ZO-2 silencing in hypertrophic tissue is due to a diminished abundance of ZO-2 mRNA, and the Sp1 transcription factor is critical for ZO-2 transcription in renal cells. Treatment of OZ rats with metformin, an activator of AMPK that blocks JNK activity, augments ZO-2 and claudin-1 expression in the liver, reduces the paracellular permeability of hepatocytes, and serum bile acid content. Our results suggest that ZO-2 silencing is a common feature of hypertrophy, and that ZO-2 is a positive regulator of the Hippo pathway that regulates cell size. Moreover, our observations highlight the importance of AMPK, JNK, and ZO-2 as therapeutic targets for blood-bile barrier dysfunction.